Allergy in Total Knee Replacement. Does it Exist?: Review Article. Issue 1 (February 2017) - Faschingbauer, Martin; Renner, Lisa; Boettner, Friedrich
Background: There is little data on whether preexisting allergies to implant materials and bone cement have an impact on the outcome of TKA. Questions/Purposes: This review article analyzes the current literature to evaluate the prevalence and importance of metal and cement allergies for patients undergoing total knee arthroplasty. Methods: A review of the literature was performed using the following search criteria: "knee, " "arthroplasty, " and "allergy" as well as "knee, " "arthroplasty, " and "hypersensitivity." Results: One hundred sixteen articles were identified on PubMed, Seventy articles could be excluded by reviewing the title and abstract leaving 46 articles to be included for this review. The majority of the studies cited patch testing as the gold standard for screening and diagnosis of hypersensitivity following TKA. There is consensus that patients with self-reported allergies against metals or bone cement and positive patch test should be treated with hypoallergenic materials or cementless TKA. Treatment options include the following: coated titanium or cobalt-chromium implants, ceramic, or zirconium oxide implants. Conclusion: Allergies against implant materials and bone cement are rare. Patch testing is recommended for patients with self-reported allergies. The use of special implants is recommended for patients with a confirmed allergy.